Testicular Teratoma in Gray Brocket Deer (Mazama gouazoubira) - Lértora, Walter Javier; Fernandez, Javier; Negrette, Marcial Sánchez (Brazilian Journal of Veterinary Pathology, 2014)
A 4-year-old gray brocket deer was submitted to bilateral orchiectomy for enlargement of the right testicle, which measured 10 x 7 x 6 cm. The testicular tumor consisted of multiple cysts containing pilosebaceous brown material and translucent mucin. Histologically, the cysts showed keratinized stratified squamous epithelium over dermal tissue with hair follicles, sebaceous and sweat glands; pseudostratified cylindrical ciliated epithelium with goblet cells, ciliated columnar epithelium and secretory columnar epithelium. Among cysts, disorganized areas of adipose tissue, arteries, nerves, neurons, smooth muscle, dense connective tissue and cartilage tissue were observed. Epithelial and mesenchymal tissues were found well differentiated. The macro and microscopic examination of the testis allowed the diagnosis of benign cystic teratoma.